Improved Blockchain Technologies for Data Storage Compared with Database: - حجّوز, محمد (Latakia University Journal -Engineering Sciences Series, 2022)
Bitcoin and its cryptocurrency equivalents have gained a special interest in the academic and business community. The technology that Bitcoin (and other cryptocurrencies, of course) depends on is blockchain technology. The essence of this technology is the distinctive data pattern it uses to keep records on the network. What distinguishes it from other methods of data preservation is its ability to keep records so that they are immutable in a way that protects the data from manipulation or forgery. To achieve this advantage, consensus mechanisms and cryptography are used, and the information is stored in a distributed node called Distributed Ledger Technology (DLT) [1]. Through this research, we will improvement this promising technology in terms of its use for storing data, and we will critically analyze its advantages and disadvantages in this context, and compared it with database.